2019
DOI: 10.1007/978-1-4939-9773-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Targets for Immunotherapy: Inhibitory T Cell Receptors

Abstract: Tumor development is characterized by the accumulation of mutational and epigenetic changes that transform normal cells and survival pathways into self-sustaining cells capable of untrammeled growth. Although multiple modalities including surgery, radiation, and chemotherapy are available for the treatment of cancer, the benefits conferred are often limited. The immune system is capable of specific, durable, and adaptable responses. However, cancers hijack immune mechanisms such as negative regulatory checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 178 publications
0
12
0
Order By: Relevance
“…Especially the initial results from the ongoing phase II study TACTI-002 on the combination of pembrolizumab with soluble LAG-3 protein showing overall response rates of 47%, are very promising ( 51 ). While most studies revealed the suppressive role of VISTA, LAG-3, and TIM-3 role in the context of T cell exhaustion ( 52 ), we uncover their suppressive role on lung tumor-infiltrated monocytes as well. Moreover, we demonstrate their upregulation of ‘don’t eat me signal’ SIRP-α too, previously shown to hamper phagocytosis upon ligation to CD47 on lung tumor cells ( 53 56 ).…”
Section: Discussionmentioning
confidence: 58%
“…Especially the initial results from the ongoing phase II study TACTI-002 on the combination of pembrolizumab with soluble LAG-3 protein showing overall response rates of 47%, are very promising ( 51 ). While most studies revealed the suppressive role of VISTA, LAG-3, and TIM-3 role in the context of T cell exhaustion ( 52 ), we uncover their suppressive role on lung tumor-infiltrated monocytes as well. Moreover, we demonstrate their upregulation of ‘don’t eat me signal’ SIRP-α too, previously shown to hamper phagocytosis upon ligation to CD47 on lung tumor cells ( 53 56 ).…”
Section: Discussionmentioning
confidence: 58%
“…This may well lead to the identification of new treatment targets, in addition to deepening our understanding of autoimmunity. Potential treatment targets include immune populations; signaling pathways of various ICIs targeting negative immune receptors (108); and secreted factors that are expanded/amplified at the initiation of the inflammatory toxicity and diminish during disease resolution, but that may not be apparent in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In a subset comprising n = 6 patients, we evaluated the surface expression of certain molecules relevant to the immune response on PBMCs, known to play a part in the antitumoral immunity and the efficacy of ICI therapy 11,16 . To differentially investigate the lymphocyte subpopulations in the peripheral blood, we used multicolor flow cytometry analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a subset comprising n = 6 patients, we evaluated the surface expression of certain molecules relevant to the immune response on PBMCs, known to play a part in the antitumoral immunity and the efficacy of ICI therapy. 11,16 To differentially investigate the lymphocyte subpopulations in the peripheral blood, we used multicolor flow cytometry analysis. Since T-cell-mediated cytotoxicity, mainly by cytotoxic T lymphocytes (CTL), expressing CD3 and CD8 at the cell surface, is considered the most important axis in lymphocyteassociated tumor control, we next focused on the CTL response in more detail, checking for cell-bound BTLA on different T-cell populations, taking special interest in CD3 + CD8 + BTLA+ cells.…”
Section: Evaluation Of Btla Surface Expression Of Pbmcs With Multicol...mentioning
confidence: 99%
See 1 more Smart Citation